Dampak Media Sosial terhadap Penegakan Hukum di Indonesia pada Era Revolusi Industri 4.0 - Sukses Marhasak Panungkunan Siburian; Melia Putri Tanisha; Theresia Titania Lai; Suhaila Zulkifli (CV WAHANA PUBLIKASI, 2026)
The rapid development of social media in the era of the Fourth Industrial Revolution has transformed public communication and significantly influenced the effectiveness of law enforcement in Indonesia. This study aims to analyze the adequacy of the existing legal framework governing social media use and examine its influence on law enforcement effectiveness. This research employs a normative legal method using statutory, conceptual, and analytical approaches through a literature review of legislation, legal doctrines, scholarly publications, and supporting data from the Central Statistics Agency (BPS) and the National Criminal Information Center (Pusiknas) of the Indonesian National Police. The findings reveal that social media positively contributes to law enforcement by enhancing transparency, accountability, public participation, crime reporting, and the use of digital evidence. However, it also presents challenges, including the rise of cybercrime, the no viral, no justice phenomenon, and trial by social media, which may undermine the independence of law enforcement officials and the application of the due process of law principle. Indonesia has established a legal framework through the Electronic Information and Transactions Law, the Personal Data Protection Law, and the new Criminal Code. Nevertheless, their implementation remains constrained by ambiguous provisions, limited harmonization among regulations, and the need to keep pace with rapid technological developments. Therefore, more adaptive legal reforms, stronger institutional capacity, and improved public digital literacy are necessary to ensure that law enforcement in the era of the Fourth Industrial Revolution remains effective, impartial, and capable of providing legal certainty.